Gain, loss, and asset pricing: It is much easier ; a note - I\~naki R. Longarela (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
Bernardo and Ledoit (2000) develop a very appealing framework to compute pricing bounds based on the so-called gain-loss ratio. Their method has many advantages and very interesting properties and so far one important drawback: the complexity of the numerical computation of the pricing bounds. In this note we provide an simple procedure for their computation which only entails solving a linear optimization program.
Keywords: C63; G12; 330; asset price bounds; gain-loss ratio; linear programming